"\\displaystyle x(x^2+y^2-a^2)dx+y(x^2+y^2-b^2)dy =0\\\\\n\n\nP = x(x^2+y^2-a^2)dx, Q = y(x^2+y^2-b^2)dy\\\\\n\n\n\\frac{\\partial P}{\\partial y} = 2xy = \\frac{\\partial Q}{\\partial x}\\\\\n\n\n\\textsf{Since}\\hspace{0.1cm} \\frac{\\partial P}{\\partial y} = \\frac{\\partial Q}{\\partial x}, \\hspace{0.1cm} \\textsf{the ODE is exact}\\\\\n\n\n\\begin{aligned}\nz &= \\int x(x^2+y^2-a^2) \\hspace{0.1cm}\\mathrm{d}x \\\\&= \\frac{x^4}{4} + \\frac{x^2 y^2}{2} - \\frac{x^2 a^2}{2} + f(y)\n\\end{aligned}\\\\\n\n\\begin{aligned}\nz &= \\int y(x^2+y^2-b^2)\\hspace{0.1cm}\\mathrm{d}y \\\\& = \\frac{y^4}{4} + \\frac{x^2 y^2}{2} - \\frac{b^2 y^2}{2} + f(x)\n\\end{aligned}\n\\\\\n\n\n\\therefore z = \\frac{x^4 + y^4}{4} + \\frac{x^2 y^2}{2} - \\frac{x^2 a^2 + b^2 y^2}{2} \\\\\\textsf{is a solution to the ODE}"
Comments
Leave a comment